1999
DOI: 10.1021/ma981766a
|View full text |Cite
|
Sign up to set email alerts
|

Influence of a Fluorescent Probe on the Local Relaxation Times for a Polystyrene Chain in the Fluorescence Depolarization Method

Abstract: The influence of the fluorescent probe on the fluorescence depolarization study was examined by using molecular dynamics (MD) simulation together with the fluorescence depolarization measurement. The relaxation times of the local motion, T m, for two series of polystyrene (PS) (r-PS and a-PS), which have different molecular structures in the vicinity of the anthryl group used as a fluorescent probe, were compared. The T m for r-PS, which has more space between the anthryl group and PS unit than a-PS, was small… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
18
0

Year Published

2000
2000
2004
2004

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…Fluorescence is a less common technique to study isolated chains in solution and detect the coil-globule transition. 11,12 However, this technique has been widely used to follow the dynamics and conformation of polymer chains in diluted solution using polymers labeled with adequate dyes, [13][14][15][16][17][18] either along the main chain, 13,18,19 on a side chain, 20 or at the chain ends. [14][15][16]21 Dipolar electronic energy transfer 22 between fluorescent groups (one donor and one acceptor) attached at specific sites has been used as a spectroscopic ruler to calculate distances between labeled sites in synthetic polymers 23,24 and biopolymers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fluorescence is a less common technique to study isolated chains in solution and detect the coil-globule transition. 11,12 However, this technique has been widely used to follow the dynamics and conformation of polymer chains in diluted solution using polymers labeled with adequate dyes, [13][14][15][16][17][18] either along the main chain, 13,18,19 on a side chain, 20 or at the chain ends. [14][15][16]21 Dipolar electronic energy transfer 22 between fluorescent groups (one donor and one acceptor) attached at specific sites has been used as a spectroscopic ruler to calculate distances between labeled sites in synthetic polymers 23,24 and biopolymers.…”
Section: Introductionmentioning
confidence: 99%
“…To avoid this problem it is necessary to work with low molecular weight polymer chains at very low concentrations, where most of the traditionally used techniques (e.g., light scattering) are not sensitive enough. Fluorescence is a less common technique to study isolated chains in solution and detect the coil−globule transition. , However, this technique has been widely used to follow the dynamics and conformation of polymer chains in diluted solution using polymers labeled with adequate dyes, either along the main chain, ,, on a side chain, or at the chain ends. , Dipolar electronic energy transfer between fluorescent groups (one donor and one acceptor) attached at specific sites has been used as a spectroscopic ruler to calculate distances between labeled sites in synthetic polymers , and biopolymers. In this case the distance between dyes should remain constant on the energy transfer time scale, otherwise the measured distances would also reflect the motion of the polymer chain. , Another type of experiment uses fluorescence anisotropy measurements of labeled polymers to provide information on the segmental motion of the chain, in the nanoseconds or subnanoseconds time range. If one is interested in the conformation and dynamics of the polymer chain instead, the time scales involved are on the order of 10 to a few hundreds of nanoseconds. Here, the formation of an excited dimer (the excimer) on the encounter of a ground-state molecule with an electronically excited molecule can also be used. , Following the time evolution of the excimer and monomer fluorescence of polymer chains labeled with an adequate fluorescent dye, we can calculate the rate constants relative to the approach of the labeled polymer segments. , From this, it is in principle possible to recover information on the dimensions of the polymer using an appropriate model.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years a great deal of effort has been devoted to understanding the local dynamics of polymers by measuring the correlation time, τ c , for segmental rotational diffusion of polymers in dilute solution. Measurement of the fluorescence depolarization of the anthracene chromophore bonded inside the main chain and measurement of 13 C NMR relaxation times and NOE values have mainly been used for this purpose. Computer simulation studies have been performed as well. It was shown that Kramers's theory in the high-friction limit resulting in eq 1 shown below with α = 1 cannot accurately describe the segmental dynamics of a synthetic polymer in dilute solutions.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years a great deal of effort has been devoted to understanding the local dynamics of polymers by measuring the correlation time, τ c , for segmental rotational diffusion of polymers in dilute solution. Measurement of the fluorescence depolarization of the anthracene chromophore bonded inside the main chain [1][2][3][4][5][6][7][8][9][10][11][12][13][14] and measurement of 13 C NMR relaxation times and NOE values [15][16][17][18][19][20][21][22][23] have mainly been used for this purpose. Computer simulation studies have been performed as well.…”
Section: Introductionmentioning
confidence: 99%
“…1 Anthryl groups have been broadly employed as polymer labels due to its well known photophysical behavior as well as to its relatively small size and high fluorescence quantum yield. 2,3 Nevertheless, it was found 4 that the chain mobility of polystyrene (PS) is slightly reduced by the steric hindrance of the anthryl group with phenyl rings and therefore, minimum proportions of labeling groups must be introduced in the polymer to preserve unmodified the macroscopic polymer characteristics. Fortunately, due to the very high sensitivity of this technique, only very low chromophore concentrations are needed, which does not disturb the system properties.…”
mentioning
confidence: 99%